Exploring the experiences of social media usage and gratification among Iraqi immigrants - Ali, Hussein Saadi Mohammed (2022)
The primary objective of this study is to investigate and explain how and why Iraqi migrants utilise social media to migrate to Europe. The reason is that social media plays an essential role through its widespread and frequent use. Several studies in the media field were performed in previous years to answer the issue of what media did to society. Meanwhile, the current study found a solution to the mentioned question about what people did with media (exploring and explaining how Iraqi immigrants use social media for illegal immigration to Europe). Mainly, the problem focuses on investigating the role of social media in influencing the behaviour of Iraqi immigrants towards migration to Europe, as well as explaining how Iraqi immigrants use media to gratify their needs and understand the motivations of individual media behaviour. This study contributed to summarising the theoretical frameworks that focused on the phenomenon of migration through a comprehensive review of the literature related to the issue of migration and the use of social networking sites in general, according to the concept of uses and gratifications in particular. This study used a Boolean search string to query journal articles' names, abstracts, and keywords. It shows the theoretical side of this study; the previous studies do not discuss unique immigrant groups but immigrants in general or the issue of immigration. Also, this study focuses on factors that influence the behaviour of the public through media when associated with studies of media effects. The study is designed to be compatible with studies of human phenomena to comply with the phenomenology approach. Moreover, it follows the method of qualitative strategies to explore the impact of social media usage on the behaviour of illegal Iraqi immigrants to Europe through the theory of uses and gratifications and phenomenology. This study used the snowball method (study sample) to search for informants. It is based on 13 in-depth interviews with Iraqi immigrants who immigrated to Europe illegally and then returned to Iraq. In this study, videos were also employed as a research tool to analyse the body language and responses of Iraqi immigrants who participated in in-depth interviews. The researcher then transcribed the data verbatim and analysed it using ATLAS.ti9 software to code the key themes, sub-themes and inter-relationships. The study's results gave insight into the role of social media in the illegal immigration of Iraqis to Europe. The potential of social media to establish an overall perception about illegal immigration to Europe is one of the most important and noticeable reasons for Iraqi immigrants' usage of social media about immigration to Europe. These theoretical findings explore the variables and factors in the theory of uses and gratification, as well as the facts and needs that make Iraqi immigrants use social media. At the same time, the practical findings are shown by seeking to develop further philosophical support for the theory of uses and gratification by proposing new models that clarify the relationship between electronic media and the society to which the message is directed to serve as a road map for workers and those interested in mass communication. This study contributed to understanding how Iraqi immigrants' usage of social media influenced their migration behaviour, as well as exploring the attractions and information supplied by social media platforms that enabled Iraqi immigrants’ decision to move and reach their destination country.